Nrega: Challenges and Opportunities: A Rights-Based Approach to Poverty Reduction and Livelihood Security (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Evolving the design of the wage employment programmes tomore effectively fight poverty, the Central Government formulated the NationalRural Employment Guarantee Act (NREGA) in 2005. With its legal framework andrights-based approach, NREGA provides employment to those who demand it and isa paradigm shift from earlier programmes. Notified on September 7, 2005, NREGAaims at enhancing livelihood security by providing at least one hundred days ofguaranteed wage employment in a financial year to every rural household whoseadult members volunteer to do unskilled manual work. The Act covered 200districts in its first phase, implemented on February 2, 2006, and was extendedto 130 additional districts from 2007. All the remaining rural areas have beennotified with effect from April 1, 2008.